ROHIS: DARI PENCARIAN IDENTITAS KE IDEOLOGISASI AGAMA - Ismatu Ropi (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2016)
ROHIS stands for Rohani (Spirit) Islam. It is school organization for religious (Islamic) activities (to develop selfpotential, creativity, religious experiences and strengthen the faith) which will be useful for the next future life. In this point, ROHIS constitutes as a new identity for Islamic students at general school. As new identity, ROHIS raised many problems. Recently, a number of intolerant behaviors in some nonreligiousbased and religiousbased schools were apparently due to ROHIS. Finally, ROHIS was also suspected as the vehicle to spread the radicalism teachings. Surprisingly, the abuse of Rohis has been a trend and it should be investigated because of involvement of religion teacher, head master and adviser of Rohis. This article discusses this problem and confers recommendation to solve it